Fathers and mothers with eating-disorder psychopathology: Associations with child eating-disorder behaviors - Lydecker, Janet A. (J Psychosom Res, 2016)
OBJECTIVE: A limited literature suggests an association between maternal eating disorders and child feeding difficulties, and notes maternal concern about inadvertently transmitting eating disorders. Thus, parents may be an important target for eating-disorder research to guide the development of clinical programs. METHODS: The current study examined differences in child eating-disorder behaviors and parental feeding practices between a sample of parents (42 fathers, 130 mothers) exhibiting core features of anorexia nervosa, bulimia nervosa, binge-eating disorder, or purging disorder, and a matched sample of parents (n=172) reporting no eating-disorder characteristics. RESULTS: Parents with eating-disorder psychopathology were significantly more likely than parents without eating-disorder characteristics to report child binge-eating and compulsive exercise. Parents with eating-disorder psychopathology reported greater perceived feeding responsibility, greater concern about their child’s weight, and more monitoring of their child’s eating than parents without eating-disorder characteristics; however, they did not differ significantly in restriction of their child’s diet and pressure-to-eat. Child body mass index z-scores did not differ between parents with versus without eating-disorder characteristics. CONCLUSION: Our findings suggest some important differences between parents with and without core eating-disorder psychopathology, which could augment clinical interventions for patients with eating disorders who are parents, or could guide pediatric eating-disorder prevention efforts. However, because our study was cross-sectional, findings could indicate increased awareness of or sensitivity to eating-disorder behaviors rather than a psychosocial cause of those behaviors. Longitudinal research and controlled trials examining prevention and intervention can clarify and address these clinical concerns.